A Siren in Babylon: the spatiality and architectures of Myra/Myron. Issue 4 (3rd April 2021) - Parreno, Christian
ABSTRACT: Myron (1974) – sequel to Myra Breckinridge (1968), the science fiction novel where Myra returns to embody Myron, after two clinical sex changes – narrates the oscillation from being male to female to male. In the story, Myron is married to Mary-Ann and living in the San Fernando Valley. Yet one night in 1973, Myra pushes Myron through the television screen while watching Siren of Babylon, transporting both not only to the production set of the movie but also to 1948. The dislocation of space and time forces Myra and Myron to live as one – as Myra/Myron, in pugnacious efforts to outline their territories. To the same extent that the female aims to reconstruct herself as a beautiful temptress who lives in a motel with tacky wooden cabins, the male strives to epitomise the prejudiced American macho who dwells in a pink-stucco Spanish-style building. Through the analysis of the metaphors of space and architecture in Myron, this paper examines the spatiality and attendant practices of two sexualities fighting to command one body. In affinity with Difference and Repetition (1968) by Gilles Deleuze, the interpretation focuses on how the perfected iteration of traditional gender roles entails particular modes of interaction with the environment.